2017
DOI: 10.21077/ijf.2017.64.2.68753-13
|View full text |Cite
|
Sign up to set email alerts
|

Process optimisation for ready to eat Indian mackerel (Rastrelliger kanagurta) curry in high impact polypropylene (HIPP) containers using still water spray retort

Abstract: Mackerel curry is a traditional food which is considered as a delicacy in Kerala. Indian mackerel curry was prepared as per standard recipe and hot filled into high impact polypropylene (HIPP) containers. Dynopack sealing machine was used for top sealing using seethrough films comprising polyester, silicone dioxide coated nylon and cast polypropylene and processed in a still water spray retort at 121.1°C to different F 0 values of 6, 7 and 8 min. Based on the sensory and commercial sterility test, F 0 value of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Chandra et al, (2012) observed the increase in TVB-N content of ribbon fish in TFS cans from 4.55 to 20.18 mg% during 5 months of storage. Dinakaran et al, (2017) reported increase in TVB-N values of mackerel curry in semi rigid containers from 14 mg% in the 1 st month to 34.7 mg% in the 14 th month of storage.…”
Section: Changes In Biochemical Characteristicsmentioning
confidence: 93%
“…Chandra et al, (2012) observed the increase in TVB-N content of ribbon fish in TFS cans from 4.55 to 20.18 mg% during 5 months of storage. Dinakaran et al, (2017) reported increase in TVB-N values of mackerel curry in semi rigid containers from 14 mg% in the 1 st month to 34.7 mg% in the 14 th month of storage.…”
Section: Changes In Biochemical Characteristicsmentioning
confidence: 93%